The Christian Architectural Complex in Cuicul between archaeological reading and engineering design - aid, Abdelhak (The Algerian Historical Journal, 2026)
Building basilicas was the most important work that Christians took care of after their religion was recognized as the official religion of the state. Architects, in the meantime, began working on adapting civil basilicas to meet the needs of Christian worship. Perhaps the most notable of these basilicas was built in the church complex in Cuicul, which was discovered during excavations in 1840 AD. It is It is one of the important architectural complexes due to its architecture, design, and the spaces it occupies. That is why I prepared the subject of the research paper entitled “The Christian Architectural Complex in Cuicul, Archaeological Reading, and Engineering Design,” trying to clarify the architectural elements and the various archaeological finds that were found in this complex.